2008
DOI: 10.1002/14651858.cd005171.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine in the maintenance treatment of bipolar disorder

Abstract: Goodwin 1994 Goodwin GM. Recurrence of mania a er lithium withdrawal. Implications for the use of lithium in the treatment of bipolar a ective disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…According to current knowledge, lamotrigine is the most effective mood stabilizer in preventing bipolar depression relapse [8,9]. Carbamazepine and its chemical derivative, oxcarbazepine, are also used in clinical practice, although their use is supported by not as strong data from controlled clinical trials [10,11]. With respect to antipsychotics, their efficacy as long-term mood stabilizers is being gradually established; however, the strongest data on atypical antipsychotics come from so-called enriched trials [12].…”
Section: Discussion the Identification Of Genetic Factors Associatedmentioning
confidence: 99%
“…According to current knowledge, lamotrigine is the most effective mood stabilizer in preventing bipolar depression relapse [8,9]. Carbamazepine and its chemical derivative, oxcarbazepine, are also used in clinical practice, although their use is supported by not as strong data from controlled clinical trials [10,11]. With respect to antipsychotics, their efficacy as long-term mood stabilizers is being gradually established; however, the strongest data on atypical antipsychotics come from so-called enriched trials [12].…”
Section: Discussion the Identification Of Genetic Factors Associatedmentioning
confidence: 99%
“…While a small RCT suggests a lack of efficacy for flupenthixol as maintenance treatment, larger studies are needed before definite conclusions can be drawn (level 3 negative) 393. Likewise, oxcarbazepine adjunctive therapy requires further evaluation (level 4) 394, 395, 396. No recommendation is made for topiramate as there is an absence of controlled data supporting its efficacy in maintenance (level 4 negative), and a lack of efficacy in acute mania381; however, its use may be indicated as it has efficacy for many syndromes that are often comorbid with BD (Section 7).…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…A second one concluded that the data for oxcarbazepine are of very low quality not allowing firm conclusions (Vasudev et al, 2008). A fair number of meta-analyses focused on lithium.…”
Section: Efficacy Datamentioning
confidence: 99%